Primarily chronic and cerebrovascular course of Lyme neuroborreliosis: case reports and literature review. Issue 1 (1st July 2000) - Wilke, Marko; Eiffert, Helmut; Christen, Hans-Jürgen; Hanefeld, Folker
Abstract : As part of an ongoing study aiming to define the clinical spectrum of neuroborreliosis in childhood, we have identified four patients with unusual clinical manifestations. Two patients suffered from a primarily chronic form of neuroborreliosis and displayed only non-specific symptoms. An 11 year old boy presented with long standing symptoms of severe weight loss and chronic headache, while the other patient had pre-existing mental and motor retardation and developed seizures and failure to thrive. Two further children who presented with acute hemiparesis as a result of cerebral ischaemic infarction had a cerebrovascular course of neuroborreliosis. One was a 15 year old girl; the other, a 5 year old boy, is to our knowledge the youngest patient described with this course of illness. Following adequate antibiotic treatment, all patients showed substantial improvement of their respective symptoms. Laboratory and magnetic resonance imaging findings as well as clinical course are discussed and the relevant literature is reviewed.